THE EFFECT OF HUMAN DEVELOPMENT INDEX, ECONOMIC GROWTH, ON POVERTY IN BENGKULU PROVINCE IN 2020-2022 (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Poverty levels remain a major concern in many developing countries, with the Human Development Index (HDI) and economic growth being important factors considered in poverty alleviation efforts. Although increasing the Human Development Index and economic growth are often considered as solutions to reduce poverty, the relationship between these factors and poverty rates needs to be studied further to better understand their impact. This study aims to analyze the effect of the Human Development Index and economic growth on the poverty rate in Bengkulu province in 2020-2022, as well as to provide a deeper understanding of these dynamics. The method used in this research is multiple linear regression analysis. The results of the analysis show that the human development index variable has a significant positive effect on poverty and economic growth has a significant negative effect on poverty. The local government could consider policies that provide public facilities to the community such as education and health, and distribute them evenly across the province. Increase investment in agricultural infrastructure such as transport networks, distribution centres, and irrigation to improve market accessibility in every region of Bengkulu province.
Keywords: Poverty; Economic Growth; Panel Data; Human Development Index